Transcriptomic screen for DIS3, DIS3L1 and DIS3L2-associated functional networks in colorectal cancer - Costa, Paulo (2025)
The final step of cytoplasmic mRNA degradation proceeds in either a 5’-3’ direction, catalyzed by XRN1, or in a 3’-5’ direction catalyzed by the exosome and DIS3L2. In yeast, DIS3/Rrp44 protein is the catalytic subunit of the exosome. In humans, there are three known paralogues of this enzyme: DIS3, DIS3L1, and DIS3L2. Important findings over the last years have shed a new light onto the mechanistic details of RNA degradation by these exoribonucleases. In addition, it has been shown that they are involved in growth, mitotic control and important human diseases, including cancer. For example, DIS3L2 inactivation was associated with mitotic abnormalities and altered expression of mitotic checkpoint proteins (1). In another study, DIS3 was found to be highly expressed in colorectal cancer (CRC), suggesting an oncogenic function (2). A major challenge in systems biology is to reveal the cellular networks that give rise to specific phenotypes (3). In this project, we aim to analyze how DIS3, DIS3L1 and DIS3L2 regulate the human transcriptome, and how their functional interactions modulate the transcriptional reprogramming of colorectal cancer cells. In order to unveil the role of these exoribonucleases in general mRNA decay, and/or in cytoplasmic mRNA surveillance mechanisms, such as nonstop- and nonsense-mediated decay (NSD and NMD), we performed their knockdown and measured the mRNA levels of various reporter transcripts (endogenous and exogenous), with emphasis in natural NMD targets. Our results show that DIS3 and DIS3L1 seem to be involved in the normal mRNA turnover, as well as in the NSD and NMD mechanisms. However, some natural NMD targets are resistant to these nucleases. On the other hand, DIS3L2 is not involved in the normal mRNA turnover or in NSD, being specifically involved in the degradation of some NMD targets. Presently, we are interested in identifying the transcript features implicated in the decision-making process of DIS3L2-mediated decay of natural NMD targets, as well as the corresponding mechanism. With this purpose, we performed a bioinformatics analysis of available transcriptomic data from DIS3, DIS3L1, DIS3L2+XRN1, XRN1, or UPF1 (a central player in NMD) knockdown experiments and identified transcripts differentially expressed in each condition. Results show some, but not total, redundancy between the upregulated transcripts, and this supports our experimental data.